Effects of Religious Behavior on Health-Related Lifestyles of Muslims in Malaysia - Siti Hasnah Hassan (Journal of religion and health, 2015)
Religion has become more prominent in shaping attitudes and behavior, but little empirical information is available on the impact of religious behavior in shaping individual Muslims health-related lifestyle behaviors in developing countries. The present study explores the relationship between religious behavior and the health-related practices of Malaysian Muslims. A convenience sample of 176 Malaysian Muslims was collected through a self-administered questionnaire. Structural equation modeling was used to develop the model. Result shows that health-related actions are strongly influenced, both directly and indirectly, by the health-related lifestyle choices consumers engaging in on a daily basis in accordance with Islamic teachings.